New techonologies : products from Phaidon design classics volume three. (London : Phaidon, 2006)
This volume follows the development of product design from the late 1960s to the present. In the last forty years, industrial design has been radically changed by the introduction of a vast array of new technologies and materials. As commercial air travel enabled individuals access to more parts of the world and colour television brought the rest of the globe into people's living rooms, communication became an increasingly important part of everyday life, inspiring the rapid development of digital culture. This has served as both a provocation and an opportunity for a new generation of product designers who see design not only as the creation of beautiful, functional objects but also as a tool to remake every aspect of contemporary life. These products, designed with and for these new technologies, have changed the way we communicate, travel, and make ourselves at home in the twenty-first century. Digital design opened up an almost endless variety of forms that has been explored and refined by innovative designers such as Philippe Starck, Ron Arad, Marc Newson and Jonathan Ive, and digital production has enabled an entirely new level of precision in manufacturing.